Crítica a la escatología de Jürgen Moltmann (Theological Kronos, 2017)
I propose a critical Reading on Jürgen Moltmann eschatology, based upon the content of two of his works: Theology of Hope, 1964, and The Coming of God, 1995. Some central elements will be highlighted, within his eschatology, taking in account the limits imposed by the space determined for this article. The framework for this critical read-ing will be Feminist Theology of Liberation, as a broad and compre-hensive framework, highlighting, in particular, the scholars Marcella Althaus-Reid, from Argentina, Ivone Gebara, Brazilian theologian and philosopher, Rosemary Radford Ruether, from US, and Elisabeth Schüssler Fiorenza, from Germany. The article is based in part on the results of a recent research work presented as Master’s Thesis in the Methodist University of São Paulo, 2011 (Brazil).
Keywords: Eschatology, Jürgen Moltmann, Feminist Theology, Theological Critic